2013
DOI: 10.1007/s00586-012-2598-z
|View full text |Cite
|
Sign up to set email alerts
|

Flexion and extension radiographic evaluation for the clearance of potential cervical spine injures in trauma patients

Abstract: Background Flexion and extension radiographs are often used in the setting of trauma to clear a cervical spine injury. The utility of such tests, however, remains to be determined. We hypothesized that in patients who underwent a negative computed tomography (CT) cervical spine scan, flexion and extension radiographs did not yield useful additional information. Methods We conducted a retrospective chart review of all patients admitted to a Level I trauma center who had a negative CT scan of the cervical spine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 20 publications
(21 reference statements)
2
37
0
7
Order By: Relevance
“…They found that 95 % of these studies were deemed inadequate as a result of either inability to visualize T1 or insufficient angulation (less than 30°) from neutral likely secondary from patient guarding [7]. Similar results were demonstrated by McCracken et al, who concluded that adequate flexion-extension films are difficult to obtain and therefore are minimally helpful in the acute setting for clearance of cervical spine trauma even in the awake and alert patient [8].…”
Section: Diagnostic Imagingsupporting
confidence: 63%
“…They found that 95 % of these studies were deemed inadequate as a result of either inability to visualize T1 or insufficient angulation (less than 30°) from neutral likely secondary from patient guarding [7]. Similar results were demonstrated by McCracken et al, who concluded that adequate flexion-extension films are difficult to obtain and therefore are minimally helpful in the acute setting for clearance of cervical spine trauma even in the awake and alert patient [8].…”
Section: Diagnostic Imagingsupporting
confidence: 63%
“…We also found that despite almost all FER being inadequate when quantitative criteria were applied; the radiologist only reported a small fraction as inadequate. Other authors have reported similarly . This suggests that a large proportion of cervical spine clearance decisions were made on the basis of suboptimal imaging.…”
Section: Discussionmentioning
confidence: 77%
“…The use of FER is controversial. FER is inadequate in 30–95% . An adequate FER is defined as one, which visualises the entire cervical spine including the C7/T1 junction and demonstrates >30° of flexion and extension .…”
Section: Introductionmentioning
confidence: 99%
“…Another paper which reduces radiation is that by McCracken et al [58] dealing with the value of flexion and extension lateral radiographs to detect instability in awake patients, with neck pain, when using CT there was no apparent injury to the neck. They retrospectively reviewed 1,000 patients, and found that adequate flexion extension films were difficult to obtain and minimally helpful in clearing the cervical spine in awake and alert trauma patients.…”
Section: Cervical Spinementioning
confidence: 99%